COMPETENCES FOR THE DEVELOPMENT OF ECODESIGN PRODUCTS. (May 2020) - Kattwinkel, D.; Bender, B.
Abstract: To respond to today's needs, engineers must be able to develop sustainable and environmentally compatible products and systems. To do so, they have to carry out new or changed activities and tasks within the product development process and therefore have to obtain new or changed competences. This publication examines which specific competences from the competence groups system thinking and communication are especially important for the development of Ecodesign products apart from technical know-how and should thus be included in a future higher education engineering course.